Критерій існування майже періодичних розв'язків нелінійних диференціальних рівнянь з імпульсним збуренням - Слюсарчук, В.Ю. (Український математичний журнал, 2015)
Получены условия существования почти периодических решений нелинейных почти периодических дифференциальных уравнений с импульсным воздействием в банаховом пространстве, не использующие H-классы этих уравнений. We establish conditions for the existence of almost periodic solutions of nonlinear almost periodic differential equations with impulsive perturbation in Banach spaces without using the H-classes of these equations.